The impact of technological progress on everyday social communications in modern society - M. A. Yuzhanin (Путеводитель предпринимателя, 2021)
In the presented article, the author examines the problems of the impact of technological progress on everyday social communications in society of the XXI century. The author analyzes the positive and negative aspects of the influence of the latest technologies on communication processes in modern society, and also touches on the topic of human interaction with artificial intelligence in the digital era. Particular attention is paid to the characteristic features of variable interactions and communications carried out through the Internet, social networks and instant messengers. As a result, it is concluded that it is necessary to form in modern generations of people a balanced, rational and critical approach to using the achievements of scientific and technological progress, not to the detriment of their intellect, independence, moral merit and the quality of communication with others, but for the good.